Age-related cerebral small vessel disease and inflammaging - Li, Tiemei (Cell Death Dis, 2020)
The continued increase in global life expectancy predicts a rising prevalence of age-related cerebral small vessel diseases (CSVD), which requires a better understanding of the underlying molecular mechanisms. In recent years, the concept of “inflammaging” has attracted increasing attention. It refers to the chronic sterile low-grade inflammation in elderly organisms and is involved in the development of a variety of age-related chronic diseases. Inflammaging is a long-term result of chronic physiological stimulation of the immune system, and various cellular and molecular mechanisms (e.g., cellular senescence, immunosenescence, mitochondrial dysfunction, defective autophagy, metaflammation, gut microbiota dysbiosis) are involved. With the deepening understanding of the etiological basis of age-related CSVD, inflammaging is considered to play an important role in its occurrence and development. One of the most critical pathophysiological mechanisms of CSVD is endothelium dysfunction and subsequent blood-brain barrier (BBB) leakage, which gives a clue in the identification of the disease by detecting circulating biological markers of BBB disruption. The regional analysis showed blood markers of vascular inflammation are often associated with deep perforating arteriopathy (DPA), while blood markers of systemic inflammation appear to be associated with cerebral amyloid angiopathy (CAA). Here, we discuss recent findings in the pathophysiology of inflammaging and their effects on the development of age-related CSVD. Furthermore, we speculate the inflammaging as a potential target for future therapeutic interventions to delay or prevent the progression of the age-related CSVD.